Checking The Hydraulic Efficiency and Improving Safety of the Internal Water Supply - Krocova, Sarka; Barcova, Karla (Communications - Scientific letters of the University of Zilina, 2018)
Water management systems in industrial facilities, industrial zones, hospitals and other internal water systems relatively frequently fail to meet the intended purpose for which they were built when an extraordinary event occurs. They may even pose a safety hazard. The causes of this condition may be of internal or external origin. Given that internal water supply systems of large premises always have a multipurpose character, i.e. to provide enough drinking water for drinking and sanitation purposes and also as a source of fire water for the fire safety of buildings, they must meet a wide range of hydraulic conditions and technical-operational capabilities. By what means and methods it is possible to achieve the desired state in economically-acceptable dimensions, while maintaining all the necessary hydraulic capabilities of the supply points of drinking and fire water, is briefly described in this article.